Balance impairment in chronic antiepileptic drug users: A twin and sibling study - Petty, S.; Hill, Keith; Haber, N.; Paton, L.; Lawrence, K.; Berkovic, S.; Seibel, M.; O'Brien, T.; Wark, J. (Wiley-Blackwell Publishing, Inc., 2010)
Purpose: Patients taking antiepileptic drugs (AEDs) have an increased incidence of fractures. This study investigated chronic AEDuse and physical contributors to falls risk using an AED-discordant, twin and sibling matched-pair approach, and assessed clinically relevant subgroups: AED polytherapy; longer-duration AED; and falls history. Methods: Twenty-nine same-sex (mean age 44.9 years, 59% female), ambulatory, community-dwelling twin and sibling pairs, discordant for AED exposure (and AED-indication), were recruited. Validated clinical and laboratory tests of strength, gait, and balance were performed. Relevant AED levels, and fasting serum samples for 25-hydroxy-vitamin D (25OHD), 1,25-dihydroxyvitamin D [1,25(OH)2D], and immunoreactive parathyroid hormone (iPTH) levels were taken. Results: There were significant mean within-pair differences in tests of static and dynamic balance, with the AED user having poorer balance function than the AED nonuser. No difference was seen in lower limb strength or gait measures. Increased duration of AED therapy and AED polytherapy were independent predictors of increased sway. No significant within-pair differences were seen in fasting serum levels of 1,25(OH)2D, 25OHD and iPTH after Bonferroni correction. Discussion: Balance performance is impaired in AED users compared to their matched nonuser siblings. Pairs where the AED users took AED polytherapy, or had a longer duration of AED use, had more impaired balance performance. These balance deficits may contribute to the increased rate of fractures in this population. © 2009 International League Against Epilepsy.